Biofilm Production of Leptospira spp. Strains - Gomes, Dayane Olímpia; Chagas, Laura Gonçalves da Silva; Ramos, Gabriela Bim; Ciuffa, Andreia Zago; Rezende, Laís Miguel; Cuccato, Lígia Pinho; dos Reis, Thais Fernanda Martins; Pires, Bruno Cabral; Lima, Anna Monteiro Correia (Acta Scientiae Veterinariae, 2018)
Background: Leptospirosis is a zoonosis that affects many species of mammals and occurs endemically in Brazil. The biofilm matrix provides structure and protection to the biofilm cells working as a physical barrier to antibiotic agents, which are attached or consumed by the matrix components. However, this attribute varies according to the matrix, antimicrobial agent and biofilm age. Leptospira may change morphologically according to environmental conditions, including cell aggregation and biofilm formation. Leptospira can colonize the ducts of kidney from hosts for a long time, forming a biofilm, which is believed to be an important factor for their maintenance in animals and in the environment. Thus, the objective of this research was to determine the biofilm formation capacity of four strains of Leptospira interrogans. Materials, Methods & Results: The strains were typified by WHO/FAO/OIE and National Collaborating Center for Reference and Research on Leptospirosis (Kit Biomedical Research, Amsterdam, Netherlands). Leptospira interrogans strains, two isolated from cattle and two isolated from dogs were biofilms tested for adhesion on polystyrene plates, extracellular matrix composition and confocal microscopy. In the plating adhesion test, the suspension was inoculated into 96-well sterile polystyrene microplates with flat bottom at a ratio of 1:200 in EMJH medium, followed by 24 h incubation at 28°C, with medium renewal after 12 h. After this period the wells were washed three times with sterile PBS and following incubation; the plates were dried in the oven at 60°C for 30 min and added 200 μL of 1% violet crystal for five min. Subsequently, the plates were washed with distilled water, after complete removal, 200 μL of acetic acid 33% was added and the readings were performed at 570 nm in the ELISA reader. The proteins and polysaccharides were quantified in a scraped pooled sample diluted in 0.85% sterile saline solution to achieve an optimal amount for testing used reagents of the BCA kit. The polysaccharide content was determined by adding into a tube, an aliquot of 0.5 mL from the pooled sample, 0.5 mL of phenol and then immediately 2.5 mL of sulfuric acid. The solution was homogenized and left to react for 15 min at room temperature. The reading was performed at 490 nm in ELISA reader. The strains were compared regarding polysaccharides and protein matrices using analysis of variance (ANOVA) and Tukey test. At confocal microscopy the strains were incubated with the tested polypropylene material for 24 h. The materials were washed with sterile phosphate buffer and stained with propidium iodide. The reading was performed using a Laser Scanning Confocal Microscope (Zeiss 710) with laser excitation (488 nm) and 580-680 nm emission filters for propidium iodide (red marking). All strains displayed strong adherence on microplate and the amount of polysaccharides in biofilm was not statistically different among the studied strains, but the amount of protein was significantly different in strain 4 (P > 0.5). The confocal microscopy showed the adherence of the Leptospira spp. strains to polypropylene material after washing. Discussion: Biofilm production plays an important role in the maintenance of a chronic infection by Leptospira interrogans with renal colonization. The exopolysaccharide (EPS) has various functions, such as checking insolubility in water; giving the three-dimensional conformation of the biofilm; protecting cells from physical (mechanical action, irradiation and temperature variations), chemical.